Associations between MTHFR gene polymorphisms (C677T and A1298C) and genetic susceptibility to prostate cancer: a systematic review and meta-analysis - You, Jianan; Huang, Yuhua; Shen, Xinyu; Chen, Yunyi; Ding, Xiang (Frontiers in Genetics, 2024)
The association between MTHFR gene polymorphisms (C677T and A1298C) and prostate cancer risk remains controversial. Methods: Two independent researchers searched the PubMed, Embase, Cochrane and Web of Science databases for all papers published up to 12/19/2023 and used various genetic models to evaluate the relationship between MTHFR polymorphisms and prostate cancer risk.The meta-analysis included 26 case-control studies with a total of 12455 cases and 13900 controls with the C677T polymorphism and 6396 cases and 8913 controls with the A1298C polymorphism. Overall, no significant association was found between the MTHFR gene polymorphisms and prostate cancer risk. However, the C677T polymorphism was associated with reduced prostate cancer risk in the Asian population (T allele vs. C allele: OR = 0.759, 95% CI 0.669-0.861, p < 0.001; TT+CT vs. CC: OR = 0.720, 95% CI 0.638-0.812, p < 0.001; TT vs. CC+CT: OR = 0.719, 95% CI 0.617-0.838, p< 0.001; TT vs. CC: OR = 0.620, 95% CI 0.522-0.737, p <0.001); however, the A1298C polymorphism was associated with an increased risk in the mixed race group from the United States (CC+AC vs. AA: OR = 1.464, 95% CI 1.052-2.037, p = 0.024; AC vs. AA: OR = 1.615, 95% CI 1.037-2.514, p = 0.034).The meta-analysis suggested that MTHFR gene polymorphisms (C677T and A1298C) may have different effects on prostate cancer risk in specific populations.